A physician's guide to the 2-dose schedule of MenB-FHbp vaccine. Issue 11 (2nd November 2019) - McDaniel, Angee; Dempsey, Amanda; Srivastava, Amit
ABSTRACT: Meningococcal serogroup B (MenB) is the predominant cause of invasive meningococcal disease in the United States, with older adolescents and young adults attending college at increased risk. Notably, MenB caused all meningococcal disease outbreaks at US colleges between 2011 and 2018. MenB disease is vaccine-preventable. The MenB-FHbp vaccine can be administered on a 2-dose (0 and 6 months) schedule to healthy adolescents and young adults or as a tailored 3-dose (0, 1–2, and 6 months) schedule for individuals at increased risk. This review focuses on the 2-dose schedule (0 and 6 months) of MenB-FHbp. Clinical evidence demonstrating strong and broadly protective immunogenicity in adolescents after primary vaccination, immune persistence up to 48 months post-primary vaccination (18–61% of subjects across schedules), and immune memory evidenced by robust response to a single booster dose are described. Implementation approaches to ensure adolescents and young adults are fully vaccinated against meningococcal disease are discussed.